Students’ Perspectives on the Use of PODCAST with Peer Assisted Learning Approach in Online Listening Classroom - Shofiyatul Huriyah; Emilia Contessa (UICELL, 2020)
Podcast with peer-assisted learning was a classroom program designed to improve awareness and encouragement for EFL listening, particularly for poorer listeners. The method of peer-assisted learning focused on interacting with peer groups or couples, providing opportunities for meaningful social experiences with Platform online Google classroom and Google meet. Podcasts were the creative media that can fulfill the needs of students and the classroom. The reason of this considers was to clarify the desires of the understudies almost utilizing Podcast with peer-assisted learning in tuning in comprehension. The sample of this study was the English Education study program for 27 students. At the end of the classroom, a questionnaire consisting of 30 questions was administered to the study group. The findings showed promising results, with most of the students believing that peer-assisted learning Podcast helps them learn listening skills. Peer-assisted learning podcasts have enhanced their vocabulary, grammar, and pronunciation and listening comprehension.